"Ser-psicológico" : uma compreensão/sentido de sua experienci-ação - Carvalho, Janne Freitas de (2006)
The present research intends to comprehend the psychologist´ s sense for his experience in action as a clinical act, through an existential phenomenological viewpoint. Therefore, this work was built to open reflexions spaces about the psychologist s action in the quotidian of his métier: how he perceives himself acting and how its attitude is constituted in the action of doing it, in spite of the place where it is acted. To elaborate the comprehension/sense, four professionals were interviewed and their narrated experiences were fundamental as reference point for the theoretical articulation. Each author/host in this research-action has contributed to reveal a felt meaning of each contextualized experience-action. One followed path pointed to a necessity to investigate some Heidegger s existential phenomenology assumptions. Other one led to interrogate the conception of clinic as an action (to act clinically) and its actual repercussions. Therefore, to think, to reflect and to articulate psychologists experiences, in different contexts, made possible to construct elaborations about the sense of to be a psychologist , about his actuation, about what is proper to him while fabricating/constructing his destination.